Breastfeeding knowledge of mothers in protracted crises: the Gaza Strip example - Iellamo Alessandro; Emily Monaghan; Samar A. L. Moghany; Jonathan Latham; Nihal Nassereddin (BMC, 2021)
Abstract The protection and support of breastfeeding is the most effective intervention to prevent child morbidity and mortality especially in humanitarian crisis. During the Palestine-Israel conflict healthcare services are understaffed and lack basic resources, with frequent power cuts and stock-outs of essential drugs and equipment. This case study seeks to answer the questions: (1) How does the protracted crisis in Gaza affect the breastfeeding practices of the most vulnerable population; and (2) What is the role that midwives can play in improving breastfeeding practices? The study was conducted using a mixed method approach with quantitative and qualitative methods. Purposeful selection of women and children was conducted utilising eligibility criteria, women with children less than 2 years of age were included. All the respondents were asked if they agreed to participate in the survey. A total of 63% practice early initiation of breastfeeding and 42% confirmed that their new-borns were given liquids other than breast milk during the first 3 days of life. Fifty percent of mothers addressed breast milk insufficiency by drinking additional fluids and 40% by using infant formula. Only 18% of women said that they received breastfeeding information during contact with health professionals throughout labour, delivery, and subsequent post-natal care visits. Many mothers during the focus group discussions (FGDs) confirm using milk to top up or replace breast milk. Myths and misconceptions around breastfeeding remain, while women do access antenatal care services and deliver in the health facilities. There is a need to a) adapt the recommendations of the operational guidance for infant and young child feeding in emergencies (IYCF-E) in the Gaza strip, to protect, promote and support breastfeeding and b) include skilled breastfeeding counselling in the pre-service and in-service training for midwives. Lessons learned included the importance of a) allocating additional research time, to account for interruption b) daily coordination with security officers to ensure safe access to localities c) identification of extra sites, in case of conflict escalation d) training of additional enumerators in case conflict escalation e) negotiation with authorities to ensure compliance with requirements.